Epidemiology of esophageal cancer in 2020 and projections to 2030 and 2040 - Liu, Chun‐Quan; Ma, Yun‐Lei; Qin, Qi; Wang, Pei‐Hao; Luo, Yi; Xu, Peng‐Fei; Cui, Yong (Thoracic cancer, 2023)
Esophageal cancer is a familiar malignancy with high incidence and mortality, and the overall prognosis is poor. The numbers of cases of and deaths from esophageal cancer have risen rapidly in recent decades. It is one of the most malignant cancers, with more than 0.6 million new cases and 0.54 million deaths worldwide in 2020. Here, we present the global epidemiology of esophageal cancer in 2020 and projections to 2030 and 2040 at different geographical levels of continents, regions and countries, and analyze them by gender, race, geographic region and human development index. We summarize the prospects for the esophageal cancer burden and risk factors in different areas, which will be useful for global esophageal cancer clinical therapy and cancer control planning. Esophageal cancer is one of the most malignant cancers, with more than 0.6 million new cases of esophageal cancer and 0.54 million deaths worldwide in 2020. In current review, we present the global epidemiology of esophageal cancer in 2020 and projections to two decades later at different levels of continents, regions and countries and analyze them in gender, race, geographic region, and human development index. Graph showed global and top 3 countries with the highest incident cases of esophageal cancer in 2020 and projections to 2030 and 2040.